Mechanical stress distribution and risk assessment of 110 kV GIS insulator considering Al2O3 settlement. Issue 1 (4th February 2019) - Liang, Hucheng; Du, Boxue; Li, Jin; Wang, Zehua
Abstract : The growing application of gas insulated switchgear (GIS) in electric power system asks for higher reliability of epoxy (EP) insulators, thus it is important to seek effective methods to improve the operating reliability of GIS insulators. On the basis of the 110 kV GIS insulator, this study studied the aluminium oxide (Al2 O3 ) settlement in the curing process and the stress distribution of the horizontally laid GIS. Besides, the risk coefficient was defined to evaluate the operating reliability of insulators laid by different methods ( I–V ). Some conclusions are shown below: the Al2 O3 settlement in the curing process causes the insulator density to have a large variation from 2.13 to 2.32 g/cm 3 . The Al2 O3 content has a great influence on the mechanical performances of EP/Al2 O3 system. The first principle stress is localised on the upper interface between the insulator and the conductor, which is the main threat to the mechanical damage of insulator. The laying method V appears to be optimal with a pretty low risk coefficient of 31.5. In actual application, for the horizontally laid GIS, the insulator should be laid with the mould gate downward to improve its mechanical reliability.